The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1089/cyber.2014.0657
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Smartphone App Use in Improving Social Capital and Reducing Social Isolation

Abstract: This study investigated the relationships among smartphone app use, social capital, and social isolation. It focused on two different smartphone apps--communication and social networking site (SNS) apps--and their effects on bonding and bridging social capital. Generational differences in smartphone use were also considered. Results from hierarchical regression analyses indicated that individuals' use of communication apps was helpful for increasing social capital and that this effect of using communication ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 23 publications
5
57
1
Order By: Relevance
“…These findings can provide researchers with opportunities to expand their understanding of the micro-mechanisms involved in adopting and using smart devices. Because previous research on smart devices has focused mostly on use among people without disabilities (Cho, 2015;Kim et al, 2011;Park and Lee, 2012), their findings cannot be fully applied to understanding what is occurring within the disabled population. Therefore, this study's main findings shed light on the contextualized and specialized mechanisms of using smart devices among this particular group of people with physical disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings can provide researchers with opportunities to expand their understanding of the micro-mechanisms involved in adopting and using smart devices. Because previous research on smart devices has focused mostly on use among people without disabilities (Cho, 2015;Kim et al, 2011;Park and Lee, 2012), their findings cannot be fully applied to understanding what is occurring within the disabled population. Therefore, this study's main findings shed light on the contextualized and specialized mechanisms of using smart devices among this particular group of people with physical disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is well known that new communication technologies, especially social media, are actively used for social interactions or creating and maintaining interpersonal relationships (Cho, 2015;Park and Lee, 2012). Particularly, research on the relationships between social media and social capital have confirmed the usefulness of such communication technologies for developing new interpersonal connections in the form of bridging social capital as well as strengthening existing personal ties or bonding social capital (Hofer and Aubert, 2013).…”
Section: Motivations For Smart Device Usementioning
confidence: 99%
See 2 more Smart Citations
“…Communication and SNS applications are effective for increasing social capital that can decrease an individual's social isolation (Cho, 2015). Furthermore, SNS and mobile communication promote offline social interaction, not replace it, by providing channels for meeting new people and talking with friends (Jacobsen & Forste, 2011).…”
Section: Adolescents' Smartphone Use Landscapesmentioning
confidence: 99%